Aspectos sociais e emocionais de mães de crianças com T21 no período de isolamento social e pós-pandêmico - Pavão, Michelle Roberta (Universidade Federal de São Carlos, 2024)
It is believed that the coronavirus pandemic contributed to changes in family functioning. Thus, the research aimed to: (a) describe the routine, needs, resources, social support, as well as anxiety and depression symptoms of family members and children with T21 during the social isolation period and the post-pandemic period based on qualitative data, according to the mothers' perspectives; (b) describe the behaviors of children with T21 during the social isolation period and the post-pandemic period based on qualitative data, according to the mothers' perspectives; (c) identify the needs, resources, and social support of families of children with T21 in the post-pandemic period based on quantitative data; and (d) analyze the relationships between variables in the post-pandemic period. The study included 20 mothers of children with T21 (from 4 to 10 years old). The instruments used were: a Family Questionnaire; the Family Needs Questionnaire (FNQ); the Social Support Questionnaire (SSQ); the Home Environment Resources Scale (HERS); and a Semi-Structured Interview Guide for families. The instruments were administered by conducting interviews on the Google Meet platform. Qualitative data were analyzed according to categories established in the interview guide. Quantitative data were analyzed using descriptive methods (measures of central tendency and dispersion). The Spearman's correlation test was used to relate the families' needs, resources, and social support. The results showed that during social isolation, families had more flexible schedules for carrying out activities, expressed a need for information, and mothers felt overwhelmed by household and family demands. Regarding emotional aspects, family members exhibited symptoms of anxiety and depression. The children experienced developmental and learning setbacks, reduced sociability, and sleep disturbances. During the return to in-person activities, families had a calmer routine, demonstrated supportiveness, and the need for information decreased. There was also a lower frequency of anxiety and depression symptoms, and the children progressed in their learning. However, they became less independent and autonomous, showing emotional attachment to parents and relatives. Considering the quantitative data, participants expressed a need for more personal time, particularly regarding the following topics “I need more friends to talk to” and “I need more opportunities to meet and speak with the parents of other children with disabilities.” They demonstrated that they had a routine with fixed schedules for daily tasks and family life, identifying spouses, friends, and children as sources of social and emotional support. Regarding the correlational data, it was found that the older the mothers, the lower the financial needs of the families. Moreover, as the children grew older, there was less of a need to explain family functioning to others. In addition, the fact of more people living in the household was associated with reduced needs for social support. Conversely, a higher number of siblings was linked to greater resources in the family environment. Social support also showed a positive correlation with family environment resources. While the issue of T21 was acknowledged, the concerns expressed by participants often did not specifically pertain to their children's needs, but rather to the pandemic as a whole. The results for the post-pandemic period indicate family needs that could be addressed by public policies focused on ensuring care for children with T21 and offering support options for family members. Although families were able to reorganize themselves, it cannot be said that this process was easy. Moreover, the historical and scientific relevance of the study is highlighted.
Social and emotional aspects experienced by mothers of children with T21 during social isolation and in post-pandemic times
Keywords: Famílias; Trissomia 21; Pandemia; Suporte Social; Necessidades; Recursos; Families; Trisomy 21; Pandemic; Social supoort; Needs; Resources; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO